Introducing the concept of creative ancestry as a means of increasing perceived fairness and satisfaction in online collaboration: An experimental study. (February 2022) - O'Leary, Kevin; Gleasure, Rob; O'Reilly, Philip; Feller, Joseph
Abstract: Online collaborations allow teams to pool knowledge from multiple domains, often across dispersed geographic locations to find innovative solutions for complex, multi-faceted problems. However, motivating individuals within online groups can prove difficult, as individual contributions are easily missed or forgotten. This study introduces the concept of creative ancestry, which describes the extent to which collaborative outputs can be traced back to the individual contributions that preceded them. We build a laboratory experiment to demonstrate the impact of creative ancestry on perceptions of fairness and output quality in online collaborations. Results from this experiment suggest the addition of creative ancestry has a positive impact on these variables and is associated with increasing perceptions of procedural justice and possibly interactional and distributive justice, dependent on the level of perceived creativity and cognitive consensus. Highlights: In an online collaboration, individuals' perceptions of procedures are closely tied to their larger sense of fairness. The addition of creative ancestry is associated with increasing perceptions of fairness in online collaboration. The technical characteristics of blockchain technologies can have a significant effect on subjective social experiences.